MINIMIZING PROCESS LEAD TIME FOR A SINGLE MACHINE USING THE DEVELOPED OPTIMAL BATCH SIZE EQUATIONS - Ruangkanjanases, A.; Vikitset, N. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Manufacturing with an optimal batch size can significantly increase production performance. In the past, complicated techniques such as optimization models, simulation, queuing theory, and complex algorithms had been explored to solve for the optimal batch size. By applying those techniques, some customizations are needed when production factors such as demands and capacity change. It is even more difficult for a plant manager to customize the model when producing more than one type of products in a single machine. In the previous research studies, none of researchers proposed the equations that a plant manager can just put the numbers into and get the optimal solution. Therefore, the developed closed-form optimal batch size equations are proposed in this research. The formula can be easily used to assess the impact of changes in production volume. The purpose is to minimize process lead time. The developed optimal batch size equation can be applied to estimate the process lead time associated with the size of the batch when the demand is given. This research provides an illustration of proposed method with various parameters applied to different products. The optimal batch size is solved and the result verifies the effectiveness of the approach.